Fitrah Manusia dalam Perspektif Al-Qur’an dan Relevansinya dalam Pendidikan Islam - Mildan, Abd. Rachman; Khulasoh, Siti (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2024)
Human nature (fitrah) is basic potential that Allah Swt has made to each individual, includes a tendency toward truth, faith, and goodness. In the Quran, human fitrah is identified as a core aspect that must be preserved and developed, as highlighted in Surah Ar-Rum [30]:30. This article examines the concept of fitrah from the Quranic perspective, exploring its definition linguistically and terminologically, alongside various manifestations of fitrah such as purity, monotheism (tauhid), and the tendency to accept the truth. The relevance of fitrah in Islamic education is a central focus, emphasizing that education aligned with fitrah can cultivate insan kamil (the complete human) through integrating spiritual, intellectual, and moral values. This Study used a descriptive qualitative method and collects data through literature study. This study was intended to provide a philosophical framework for Islamic education in designing teaching methods that not only focus on academics but also foster holistic character development. The findings are expected to serve as a key reference for educational practitioners in creating balanced approaches to worldly and spiritual aspirations. Keywords: Human Nature, Qur’an; Islamic Education; Insan Kamil; Spiritual Values